PERBANDINGAN HASIL BELAJAR SISWA ANTARA PENERAPAN MODEL INKUIRI MENGGUNAKAN MEDIA CD GAME DENGAN MODEL PROBLEM BAS - Sopian, Yopi (2011)
The learning outcomes of students will meet the ideal expectation governed by school. In fact, SMK learning outcomes microcontroller subject is below the competency standard requirement. One of reasons is the lack of learning program needed by the students. This research uses experiment methods non-equivalent (pre test and post test) control group design. Subject of the research is students of XII Electronic Industry A, as a class experiment whom given a treatment by which applying inquiry learning model, using Compact Disk (CD) game interactive multimedia along with students of XII Electronic Industry B, as a class control to whom they are given the treatment model Problem Based Learning (PBL). The instrument it self is multiple choice test, a performance test, and a observer. Number of Reliability test in the amount 0.97. Data analysis uses t test. The result will be found the difference on cognitive aspect of the learning outcomes between class of experiment with control class. The experiment class increase the number (Gain of 38,6 with N-Gain in the amount of 68,1), while the class control increase Gain in the amount of 35,4 with N-Gain in the amount of 61,7. The other finding finds no difference in learning outcome of the students on psychomotor aspect. As for the learning outcome of affective aspect show the positive attitude and student response toward the learning project. Moreover, it gains the students interest in experiment class by applying media of CD game interactive multimedia. in conclusion to the research. It show that the result of learning outcome increases after applying inquiry model using media CD game interactive multimedia. However, it suggest for those schools, which have sufficient facilities of Information and Communication Technology (ICT).